A Study of Anxiety on English Speaking in Classroom of Year Four Students at The Faculty of Languages Souphanouvong University: https://doi.org/10.69692/SUJMRD090118 - BOUNTHAVONG , Oudalon; LAMPHAIPHANH , Ketsalinh; CHANBOUALAPHA, Phonexay; PHEWYUPHINE, Pheth (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The objective of this study was to study anxiety on English speaking in classroom of year 4 students and the main cause of students’ anxiety on English speaking at the Faculty of Languages, Souphanouvong University. It was a quantitative study and the participants were the 36 students in fourth year from department of Foreign Language, Faculty of Languages, Souphanouvong University. The instrument was a questionnaire, consisting of 22 items about anxiety on English speaking and the main cause of students’ anxiety on English speaking. The Mean and Standard Deviation used SPSS Program to analyze the data. The finding of the study: Students have problems in English speaking during class because they get nervous when speaking English as shown in the items of advice and self-report, answering their teachers’ questions and students feel very self-conscious about speaking English in front of others friends in class, students worry and make mistakes and are afraid that their classmates will laugh at them. The main cause of students’ anxiety on English speaking in classroom is that students are anxious to speak English in class, because they have lack of flexibility of words, concerns for their ideas. Also, students have lack of words and experience in pronunciation, with the Mean of3.86 and S.D of 0.961. Moreover, students are afraid of making mistakes in grammar and structure of sentence.